Writing(s) at the Crossroads The process-product interface - Cislaru, Georgeta (John Benjamins Publishing Company, 2015)
This volume aims at contributing to an interpretive approach to writing and its dynamics. It offers a general scope on the process-product interface by multiplying the points of view on both the process and the product and their links. The book presents new findings and perspectives in the study of language and writing, both theoretical and methodological (e.g. dual process models of writing, pragmatics of writing, linguistic analysis of psycholinguistic units such as bursts of production). It also presents new tools for a longitudinal approach to the writing steps, key-stroke logging with integrated linguistic modules, and textometric analysis of written texts. The volume is composed of five sections that highlight different approaches to writing from the viewpoint of multiple disciplines: Anthropology, Cognitive Psycholinguistics, Communication Studies, Didactics (Applied Linguistics), Discourse Analysis, Literacy, Sociolinguistics and Text Genetics.